Wi-Fi™, Bluetooth™, Zigbee™ and WiMax™ - Labiod, Houda; Afifi, Hossam; de Santis, Costantino (Springer Netherlands : Imprint: Springer, 2007)
Wi-Fi™, Bluetooth™, ZigBee™ and WiMax™ will provide a complete and detailed description of the recent wireless technologies including Wi-Fi, Bluetooth, ZigBee and WiMAX. These technologies are considered to be important topics in the telecommunication industry in the next decade. Some critical subjects will be particularly developed such as security, quality of service, roaming and power conservation. Wi-Fi™, Bluetooth™, ZigBee™ and WiMax™will also include some chapters on practicals aspects.